Viral escape from endosomes and host detection at a glance - Staring, Jacqueline; Raaben, Matthijs; Brummelkamp, Thijn R (Journal of cell science, 2018)
In order to replicate, most pathogens need to enter their target cells. Many viruses enter the host cell through an endocytic pathway and hijack endosomes for their journey towards sites of replication. For delivery of their genome to the host cell cytoplasm and to avoid degradation, viruses have to escape this endosomal compartment without host detection. Viruses have developed complex mechanisms to penetrate the endosomal membrane and have evolved to co-opt several host factors to facilitate endosomal escape. Conversely, there is an extensive variety of cellular mechanisms to counteract or impede viral replication. At the level of cell entry, there are cellular defense mechanisms that recognize endosomal membrane damage caused by virus-induced membrane fusion and pore formation, as well as restriction factors that block these processes. In this Cell Science at a Glance article and accompanying poster, we describe the different mechanisms that viruses have evolved to escape the endosomal compartment, as well as the counteracting cellular protection mechanisms. We provide examples for enveloped and non-enveloped viruses, for which we discuss some unique and unexpected cellular responses to virus-entry-induced membrane damage.